Differences

This shows you the differences between two versions of the page.

Link to this comparison view

Both sides previous revision Previous revision
predicate_logic [2016/05/01 15:38]
nikolaj
predicate_logic [2016/05/01 15:56] (current)
nikolaj
Line 45: Line 45:
 I came up with  I came up with 
  
-$P(!a) \equiv \left(\forall x.\,P(x)\implies x=a\right)$ ​+$\phi(!a) \equiv \phi(a) \land \forall x.\left(\phi(x)\implies x=a\right)$ ​
  
-for a predicate $P$, expressing that $P$ only holds for the term $a$.+for a predicate $P$, expressing that $P$ only holds for the term $a$. Then 
 + 
 +$\exists! x.\,\phi(x) \equiv \exists x.\,​\phi(!x)$
  
 We also use the abbreviation ​ We also use the abbreviation ​
Link to graph
Log In
Improvements of the human condition